Reliability and Validity of Beliefs about Substance Use (BSU) Questionnaire in Alcohol Dependent Patients. - Selçuk ASLAN; M. Hakan TÜRKÇAPAR; Hale Yapıcı ESER; Mustafa UĞURLU (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: In this study, it is aimed to evaluate the validity and reliability of the Beliefs About Substance Use Questionnaire (BSU) which was originally developed by Wright (1993). Method: Seventy alcohol addicted inpatients, who were admitted to Ankara Dışkapı Yıldırım Beyazıt Education and Research Hospital Psychiatry Clinic, 31 healthy volunteers who had never used alcohol and 33 social drinkers were evaluated. For all groups, BSU and Craving Beliefs Questionnaire (CBQ), for the patient groups, Beck Anxiety Inventory (BAI), Clinical Institute Withdrawal Assessment (CIWA), Dysfunctional Attitudes Questionnaire (DAS) and Automatic Thoughts Questionnaire (ATQ) were used as the assessment tools. The correlations and differences between the questionnaires were studied. Results: Mean age of the addicted patients, healthy controls and social drinkers were 42,3± 7,0, 33,5± 9,9 and 33,2± 8,9, respectively. In patient group, mean BSU score was 46,4 ± 21,2. For alcohol addicts, internal reliability of BSU was found to be adequate (Cronbach alfa=0.91) and item-total score correlations were between 0.33 and 0.69. Basic component analysis showed one basic factor. A positive correlation has been found between BSU and CBQ, and ATQ scores. No correlations have been found between total and subscale scores of DAS and total scores of CIWA, BAI and BSU. In evaluation of validity, BSU mean scores of alcohol addicts were found to be significantly higher than healthy controls and social drinkers. Conclusion: Our findings support that Turkish version of BSU is an adequate tool that can be used to evaluate alcohol addicted patients` cognitive believes about alcohol use